2018
DOI: 10.1021/acs.est.8b03236
|View full text |Cite
|
Sign up to set email alerts
|

XANES-Based Determination of Redox Potentials Imposed by Steel Corrosion Products in Cement-Based Media

Abstract: The redox potential (Eh) in a cementitious nuclear waste repository is critical to the retardation behavior of redox-sensitive radionuclides (RNs), and largely controlled by embedded steel corrosion but hard to be determined experimentally. Here, we propose an innovative Eh determination method based on chemical/spectroscopic measurements. Oxidized nuclides (U, Se, Mo, and Sb) were employed as species probes to detect the Eh values imposed by steel (Fe) and steel corrosion products (magnetite/hematite, and mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…The comparative study of XANES is based on the fact that similar XANES spectra often indicate similar chemical environment, since a XANES spectrum contains abundant features that often alter due to a change of neighboring atoms or their coordination geometry [29]. This has been extensively demonstrated for cementitious systems [30][31][32][33][34]. Here, eight points of interests (POIs) were selected for XANES measurements along the veins of ASR products in ES1, ES2 and N1, in a way that the measured spots move from crystalline region to amorphous region, as shown in Figure 2.…”
Section: Micro-xasmentioning
confidence: 99%
“…The comparative study of XANES is based on the fact that similar XANES spectra often indicate similar chemical environment, since a XANES spectrum contains abundant features that often alter due to a change of neighboring atoms or their coordination geometry [29]. This has been extensively demonstrated for cementitious systems [30][31][32][33][34]. Here, eight points of interests (POIs) were selected for XANES measurements along the veins of ASR products in ES1, ES2 and N1, in a way that the measured spots move from crystalline region to amorphous region, as shown in Figure 2.…”
Section: Micro-xasmentioning
confidence: 99%
“…A similar phenomenon was observed in the case of M/G (Figure 3c). In addition, the selenium sorbed species have been investigated in our previous work, [20] showing that at least ~50% sorbed Se(IV) was reduced under similar experimental conditions. The study indicated that both Fe(0) and magnetite still showed strong reducing ability towards Se(IV) in hyperalkaline CPW.…”
Section: Reducibility Of Steel Corrosion Products Towards Se(iv)mentioning
confidence: 89%
“…Fe 0 and its corrosion products can also immobilize Se(IV) through reductive precipitation and surface adsorption (inner-sphere complexation in most cases). [19,20] Furthermore, most CEM-V/A cement probably contains Fe-(oxyhydr)oxides and metal (bi)sulfides, which originate from the blended BFS and FA, and which are effective for RNs removal. As previously reported, under acidic to slightly alkaline conditions, Fe-(bi)sulfides (e.g., pyrite, [21] pyrrhotite, [22] greigite, [14,23] and mackinawite [24]) are able to efficiently immobilize Se(IV), resulting in Se(0), FeSe, and/or FeSe 2 reduction products.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…In reductive precipitation processes, Fe II -bearing minerals catalyze the reduction of Se IV forming predominantly Se 0 , but also Fe selenides (FeSe, and FeSe2) depending on the experimental conditions. 36,37,39,77,78 In adsorption processes, sorbed Se IV may form inner-sphere (FeSeO3) and outer-sphere (Na2SeO3 electrostatic sorption) complexes. 77,[79][80][81] Although Se IV is generally sorbed by bidentate inner-sphere complexation, 78 the exact Se IV solid species in our system are hard to describe by our XANES measurements.…”
Section: S10b)mentioning
confidence: 99%